2019
DOI: 10.1038/s41598-019-53638-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological characterization of Lemur tyrosine kinase 2 (LMTK2) in Alzheimer’s disease and neocortical Lewy body disease

Abstract: Alzheimer’s disease (AD) and neocortical Lewy body disease (LBD) are the most common neurodegenerative dementias, with no available curative treatment. Elucidating pathomechanism and identifying novel therapeutic targets are of paramount importance. Lemur tyrosine kinase 2 (LMTK2) is involved in several physiological and pathological cellular processes. Herewith a neuropathological characterization is presented in AD and neocortical LBD samples using chromogenic and fluorescent LMTK2 immunohistochemistry on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
2
15
0
1
Order By: Relevance
“…In accordance with our findings, recent studies have shown decreased LMTK2 level in AD [12,13,19]. A genome-wide gene expression analysis detected reduced LMTK2 expression in the cortex of transgenic Tau P301L mice [19].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In accordance with our findings, recent studies have shown decreased LMTK2 level in AD [12,13,19]. A genome-wide gene expression analysis detected reduced LMTK2 expression in the cortex of transgenic Tau P301L mice [19].…”
Section: Discussionsupporting
confidence: 93%
“…Alterations of LMTK2 level may contribute to neurodegeneration by disrupted axonal transport, enhanced apoptosis and tau hyperphosphorylation [11]. We previously described decreased LMTK2 level in human postmortem AD brains compared to age-matched controls [13]. Our immunohistochemical (IHC) results were in accordance with other human and animal model studies [12,19].…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations